Value creation or value destruction: Conceptualizing the experiential nature of value-in-use - Abid, M.F. (John Wiley and Sons Ltd, 2022)
The studies to date on service research have provided a generic overview on customer's positive value-in-use (value creation) as well as negative value-in-use (value destruction). Surprisingly, very little attention is made to exploring the experiential nature of value-in-use. This study aims to conceptualize the experiential nature of value-in-use where positive value-in-use results in value destruction in some situations (and value creation commonly), and negative value-in-use results in value creation in some situations (and value destruction normally). By integrating value-in-experience and value-in-context, the study proposed experience-dominant logic (EDL) as an important paradigm for value creation in the customer journey. The EDL is backed by the four foundational premises for which the insights are taken from literature as well as through in-depth interviews with customers and managers of the E-beauty services. The research also provides a framework for future research avenues as well as various future research directions. Â© 2022 John Wiley & Sons Ltd.